2014
DOI: 10.1002/2014jd021891
|View full text |Cite
|
Sign up to set email alerts
|

Temporal variations of atmospheric water vapor δD and δ18O above an arid artificial oasis cropland in the Heihe River Basin

Abstract: The high temporal resolution measurements of δD, δ 18 O, and deuterium excess (d ) of atmospheric water vapor provide an improved understanding of atmospheric and ecohydrological processes at ecosystem to global scales. In this study, δD, δ 18O, and d of water vapor and their flux ratios were continuously measured from May to September 2012 using an in situ technique above an arid artificial oasis in the Heihe River Basin, which has a typical continental arid climate. The monthly δD and δ 18O increased slowly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
79
2
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(96 citation statements)
references
References 96 publications
(185 reference statements)
13
79
2
2
Order By: Relevance
“…Gates et al, 2008a;Ma et al, 2008Ma et al, , 2009Ma et al, , 2012Huang and Wen, 2014) and atmosphericcirculation modelling studies (e.g. Gao et al, 2004;Chu et al, 2005;Meng et al, 2009Meng et al, , 2012Meng et al, , 2015Wen et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Gates et al, 2008a;Ma et al, 2008Ma et al, , 2009Ma et al, , 2012Huang and Wen, 2014) and atmosphericcirculation modelling studies (e.g. Gao et al, 2004;Chu et al, 2005;Meng et al, 2009Meng et al, , 2012Meng et al, , 2015Wen et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Considering water vapor as a mixture of ET from an ecosystem that carried unique isotopic signals from plant transpiration and soil evaporation separately, the measured isotopic composition of water was used to partition ET into evaporation and transpiration. Details of the isotope experiment and its calibration procedure are given by Huang and Wen [62] and Wen et al [63]. In this study, the ratio of T over ET was collected to evaluate the reliability of three TSEB models on evaporation and transpiration partitioning.…”
Section: Hiwater-musoexe Campaign and Ground-based Measurementsmentioning
confidence: 99%
“…The maximum leaf area index (LAI) was 5.6 m 2 /m 2 and the canopy average height was 2.1 m. The experiment was conducted between 28 May and 21 September 2012. More details of the study site can be found from Huang and Wen (2014) and Yang et al (2015).…”
Section: Study Areamentioning
confidence: 99%
“…In this study, the flux-profile method was used to measure the water vapor flux in Zhangye (Huang and Wen, 2014), which was based on the data taken from wavelength-scanned cavity ring-down spectroscopy (Model L1102-i, Picarro Inc., USA) and tunable diode laser absorption spectroscopy (Model TGA100A, Campbell Scientific Inc., USA) in Luancheng . In the experiment, the two intakes were set to 0.5 and 1.5 m above the canopy and adjusted following the canopy growth.…”
Section: Water Vapor Flux and Micrometeorological Observationmentioning
confidence: 99%